2011 8th International Symposium on Wireless Communication Systems 2011
DOI: 10.1109/iswcs.2011.6125268
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the space of functions analog-computable via wireless multiple-access channels

Abstract: To efficiently compute linear functions of the measurements in sensor networks, it was recently shown that the superposition property of the wireless multiple-access channel can profitably be exploited. Using suitable pre - and postprocessing functions operating on real sensor readings and on the superimposed signal received by a fusion center, respectively, the natural computation property of the wireless channel can be adapted such that a much larger class of functions is efficiently computable as well. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…The identity map on any set A is described by idA : A → A. Definition 1 (Nomographic Functions [5]). Let A k , k ≥ 2, be a metric space.…”
Section: Notational Remarksmentioning
confidence: 99%
See 4 more Smart Citations
“…The identity map on any set A is described by idA : A → A. Definition 1 (Nomographic Functions [5]). Let A k , k ≥ 2, be a metric space.…”
Section: Notational Remarksmentioning
confidence: 99%
“…In [5] we have shown that every f ∈ F[E n ] is essentially computable by exploiting the superposition property of a wireless MAC (i.e., mathematically N [E n ] ≡ F[E n ]). The surprising fact was that the pre-processing functions are universal and thus independent of the desired function.…”
Section: Universality and Robustnessmentioning
confidence: 99%
See 3 more Smart Citations